2010
DOI: 10.1007/s13139-009-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between 18F-FDG PET/CT and EMG Mapping for Identifying Dystonic Superficial Muscles in Primary Cervical Dystonia: Preliminary Results

Abstract: Purpose This study was conducted to compare 18 F-FDG PET/CT and electromyography (EMG) mapping in patients with primary cervical dystonia (PCD) to find dystonic superficial cervical muscles. Methods Ten consecutive patients with PCD (M:F=5:5, age 44±13 years) whose dystonic posture was not relieved with conventional muscle relaxant therapy were included. Target cervical muscles for the comparison between 18 F-FDG PET/CT and EMG mapping were four representative superficial bilateral cervical muscles: splenius c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…[4,5] Preoperatively and postoperatively, dystonic muscles are readily detected by 18 F-FDG PET/CT and SPECT/CT. [1][2][3] In the present case, an abnormal FDG uptake in the right obliquus capitis inferior was detected through preoperative 18 F-FDG-PET/CT. Following an SPD including an intradural rhizotomy of the anterior C1 and C2 nerve roots, the patient became asymptomatic.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…[4,5] Preoperatively and postoperatively, dystonic muscles are readily detected by 18 F-FDG PET/CT and SPECT/CT. [1][2][3] In the present case, an abnormal FDG uptake in the right obliquus capitis inferior was detected through preoperative 18 F-FDG-PET/CT. Following an SPD including an intradural rhizotomy of the anterior C1 and C2 nerve roots, the patient became asymptomatic.…”
Section: Discussionsupporting
confidence: 46%
“…Preoperatively and postoperatively, dystonic muscles can be identified utilizing 18F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/ computed tomography (PET/CT). [2,3] Here, a patient underwent selective peripheral denervation (SPD) followed by resolution of dystonia and 18 F-FDG-PET/CT findings thus confirming the effectiveness of the surgery.…”
Section: Introductionmentioning
confidence: 68%
“…13,15) The identification of dystonic muscles is essential for maximizing the efficacy of cervical dystonia treatment. 3) The dystonic muscles are identified based on clinical symptoms and physical examination; however, they can also be detected by EMG, 18 F-FDG PET/CT and SPECT/ CT. [5][6][7] Jang et al reported that the sensitivity, specificity, and accuracy of 18 F-FDG PET/CT for localizing dystonic muscles were 76%, 92%, and 88%, respectively. 5) In the present case, abnormal FDG uptake in the left obliquus capitis inferior was detected on preoperative 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“… 4 ) 18F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) is a noninvasive modality that has been used to identify dystonic muscles in cervical dystonia. 5 , 6 ) Recently, single photon emission computed tomography (SPECT/CT) was reported to successfully identify dystonic muscles. 7 ) These examinations support the identification of dystonic muscles and increase the efficacy of BT injections.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is an invasive technique and it does not help clinicians to predetermine the dystonic muscles [8].Other methods, such as sonography and computed tomography reflects only the anatomical structure of the muscle but not the function [9]. A Korean research group proved that 18 F-Fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET/CT) could be useful for detecting dystonic muscles [10][11][12]. However, its use is limited by its accessibility and price.…”
Section: Introductionmentioning
confidence: 99%